PENERAPAN TATA RUANG KANTOR DALAM MENGOPTIMALKAN KINERJA TENAGA PENDIDIK DI MAN 6 PIDIE - Hasbi, Subhan; Mutia, Sri; Ela Safira, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of office space in optimizing the performance of educators at MAN 6 Pidie. This research is motivated by the limitations of workspace, the arrangement of facilities that are not optimal, and social dynamics in the teacher's work environment that affect the comfort and effectiveness of work. In addition, previous research used a more quantitative approach so that there is still a research gap related to educators' subjective experience of the work environment in depth. This study uses a descriptive qualitative approach. The research subjects consisted of the head of the madrasah, the deputy head of facilities and infrastructure, teachers, and administrative staff who were selected through purposive sampling techniques. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used Miles and Huberman's interactive model. The results of the study show that the office layout at MAN 6 Pidie has been adjusted based on the work function of each unit, but still faces limited space, facilities, and budget. Nevertheless, harmonious interpersonal relationships and a collective work culture are able to create a comfortable work environment and support the optimization of the performance of educators. The results of this study show that office spatial planning not only affects physical comfort, but also the effectiveness of coordination, concentration, and work productivity of educators.